Justice profiles in Europe: Major differences in evaluation of inequality - Cristóbal Moya; Jule Adriaans (DIW Weekly Report, 2022)
European societies have been experiencing growing income and wealth inequalities over the past few decades, and, accordingly, they are a topic of intense discussion. Although the population's evaluation of inequalities as just or unjust is important for designing social policies, there has been little research on this evaluation. To close this gap, we use justice evaluations of income and wealth in the European Social Survey (2018/2019). We identify four types of justice profiles among the active working population in Europe: critics, altruists, the deprived, and status quo supporters. These groups differ in terms of if and where they perceive injustice in the income and wealth distributions. Most respondents are either critics, who perceive injustice in all dimensions and support redistribution, or altruists, who assess their own situation as just but the societal income and wealth differences as unjust. Policymakers should address the widespread concern about social justice and consider where injustice is perceived in the income and wealth distributions when designing policies.
Keywords: D31; D63; J30; 330; Social justice; Income and wealth inequalities; Europe